2020
DOI: 10.1021/acs.est.9b07835
|View full text |Cite
|
Sign up to set email alerts
|

Chemolithoautotropic Diazotrophy Dominates the Nitrogen Fixation Process in Mine Tailings

Abstract: Nutrient deficiency, especially bio-available nitrogen deficiency, often impedes the bioremediation efforts of mining generated tailings. Biological nitrogen fixation is a critical process necessary for the initial nitrogen buildup in tailings. Current knowledge regarding the diazotrophs that inhabit tailings is still in its infancy. Therefore, in this study, a comprehensive investigation combining geochemical characterization, sequence analyses, molecular techniques, and activity measurements was conducted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 87 publications
5
55
0
Order By: Relevance
“…In our study, four top OTUs were related to Ferrovum myxofaciens, including OTU833 (9.76%), OTU839 (4.27%), OTU796 (0.76%), and OTU450 (0.71%), with a total relative abundance of up to 15.50%, indicating the presence of considerable amounts of autotrophic bacteria with iron oxidation and nitrogen xation abilities in contaminated soil. This can be attributed to a survival strategy of bacteria in a strongly acidic and oligonitrogenous environment, which provides carbon and nitrogen sources for cell survival through autotrophic carbon xation and carbon sequestration(Sun et al 2020b). OTU835 and OTU322 were identi ed to be similar to Acidithiobacillus ferrooxidans, an acidophilic chemolithoautotrophic bacterium that can grow by oxidizing Fe(II) and reducing sulfur compounds(Jin et al 2020).…”
mentioning
confidence: 99%
“…In our study, four top OTUs were related to Ferrovum myxofaciens, including OTU833 (9.76%), OTU839 (4.27%), OTU796 (0.76%), and OTU450 (0.71%), with a total relative abundance of up to 15.50%, indicating the presence of considerable amounts of autotrophic bacteria with iron oxidation and nitrogen xation abilities in contaminated soil. This can be attributed to a survival strategy of bacteria in a strongly acidic and oligonitrogenous environment, which provides carbon and nitrogen sources for cell survival through autotrophic carbon xation and carbon sequestration(Sun et al 2020b). OTU835 and OTU322 were identi ed to be similar to Acidithiobacillus ferrooxidans, an acidophilic chemolithoautotrophic bacterium that can grow by oxidizing Fe(II) and reducing sulfur compounds(Jin et al 2020).…”
mentioning
confidence: 99%
“…To gain a deeper insight on the rare portion of the gammaproteobacterial diversity, we conducted a higher-level taxonomic resolution analysis, which indicated that a total of eight gammaproteobacterial families were actually not rare locally (i.e., >1% contribution in at least one site), including Cycloclasticaceae, Halieaceae, KI89A clade, Nitrincolaceae, Rhodocyclaceae, Thioalkalispiraceae, Thiotrichaceae, and UBA10353 marine group (Figure 4B). All of these families include members recently reported to be particularly abundant in naturally-rich and/or contaminated environments that display high concentrations of HMs and/or hydrocarbons (Gołębiewski et al, 2014;Singleton et al, 2015;Yang et al, 2016Yang et al, , 2020Suzuki et al, 2019;Bergo et al, 2020;Noirungsee et al, 2020;Sun et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, a higher proportion of aerobes were noted in diazotrophic community of Fe-accumuli soils as comparing with that in Hapli-type soils ( Figure S12), which might be linked with the NH 4 + -N storage in anaerobic paddy soils of Fe-type soil with weak N 2 xing ability. The phylogenetic a liation and formation mechanism of the presence of these aerobic diazotrophs will be further explored combined with omics and N 2 xation activity analysis (acetylene reduction assay and 15 N-isotope techniques) [23,24] .…”
Section: Discussionmentioning
confidence: 99%
“…4B). Sulfur reducing and oxidizing microorganisms have been reported to act as active N 2 xers in ecosystems, such as in sul dic sediment [23,55,56] . The obligate anaerobe, Desulfobacca belonging to Syntrophaceae, has been identi ed as major acetate-degrading SRB and common N 2 xers in paddy soil [24,57] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation